Dancing from the inside out : using design thinking to explore the intersections of street dance, social media, and self-identity in Aotearoa : an exegesis presented in partial fulfilment of the requirements for the degree of Master of Design, Massey University, College of Creative Arts, Wellington, New Zealand - Smith, Phoebe J (Massey University, 2016)
Street dance, derived from hip hop dance, is a vehicle for self-expression, connecting with others, understanding purpose, promoting confidence, challenging and improving oneself, and positively impacting participants’ lives (Henderson, 2010). Beyond a form of physical activity, it holds much potential to influence self-identity. Since the advent of YouTube in 2005, social media platforms—particularly YouTube, Facebook, Twitter, and Instagram—have become central to street dance culture’s production and consumption. These networked mediascapes have increased the culture’s visibility, accessibility, participation, and provided a platform to share dance expression, join the international street dance community, as well as access or even create professional opportunities. The way street dance cultural flows circulate through social networking sites recursively shape and inform the culture itself. Dancing from the Inside Out uses design thinking methods to investigate how engagement with street dance culture in networked spaces—where self-identity is performed, actively constructed, and negotiated—might impact an individual’s relationship with street dance. Following empathy research, the project uses the Māori health and wellness model Te Whare Tapa Whā as an analytical framework, and identifies an opportunity to strengthen one’s taha wairua, or spiritual wellbeing, concerning ideas around self-expression and understanding identity. These concepts are at the heart of street dance culture and promote identity development, though risk being overridden by emerging cultural practices that digitally networked spaces have shaped. The project’s design response takes the form of Hikoi (Māori term meaning to step, stride, march)—the initiation of a movement starting in online social networking environments, in pursuit of the heart and soul of street dance. A practice-based design investigation, Hikoi movement builds a narrative across Facebook and Instagram, and using video portraits, blog posts, and still images, that adhere to a manifesto, aims to inform and inspire Aotearoa street dancers about strengthening taha wairua, in the age of social media.
Keywords: Dance; Street dance; Hip-hop dance; Design; Social aspects; Social media; Identity; New Zealand; Research Subject Categories::HUMANITIES and RELIGION::Aesthetic subjects